2010
DOI: 10.4103/0253-7613.66843
|View full text |Cite
|
Sign up to set email alerts
|

Cleistanthus collinus induces type I distal renal tubular acidosis and type II respiratory failure in rats

Abstract: Background and Purpose:A water decoction of the poisonous shrub Cleistanthus collinus is used for suicidal purposes. The mortality rate is 28%. The clinical profile includes distal renal tubular acidosis (DRTA) and respiratory failure. The mechanism of toxicity is unclear.Objectives:To demonstrate features of C. collinus toxicity in a rat model and to identify its mechanism(s) of action.Materials and Methods:Rats were anesthetized and the carotid artery was cannulated. Electrocardiogram and respiratory movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…The terminal event in these test rats was respiratory arrest with bradycardia, and subsequent cardiac arrest. [ 56 ] The type 2 respiratory failure could be explained by the presence of neuromuscular blockade. This study did not demonstrate the occurrence of ECG abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The terminal event in these test rats was respiratory arrest with bradycardia, and subsequent cardiac arrest. [ 56 ] The type 2 respiratory failure could be explained by the presence of neuromuscular blockade. This study did not demonstrate the occurrence of ECG abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…This study did not demonstrate the occurrence of ECG abnormalities. [ 56 ] Another study which examined the effect of the boiled extract on the rat heart had different observations. The study showed that low doses of extract caused transient tachycardia with increased myocardial contractility, while high doses caused arrhythmia and cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 ] The leaf extract of C. collinus produced type I distal renal tubular acidosis and type II respiratory failure in preclinical evaluations, and it was suggested that these changes are due to a decrease in the pH value of the urine, a failure of the acid-secreting mechanism and a decrease in the blood potassium levels. [ 16 ] In this study, no changes in urinary pH value (acidity) were observed with either cleistanthin A or cleistanthin B. As discussed earlier, one or more compounds other than cleistanthin A or cleistanthin B present in the leaf extract may be responsible for the acidosis and other effects on the kidneys.…”
Section: Discussionmentioning
confidence: 42%
“…The use of a C. collinus leaf extract is reported to have reduced the urinary pH value. [ 16 ] Since the leaves of C. collinus contain more than 30 compounds, it is possible that the reduction in pH was due to one or more compounds other than cleistanthins A and B. Although the compounds exert a diuretic activity as indicated by the diuretic index being greater than one, the extent of the effect is not comparable with that of furosemide.…”
Section: Discussionmentioning
confidence: 99%
“…that no evidence of cardiotoxicty was found in rats when the crude extract was given, and the present study also show similar results. [ 37 ]…”
Section: Discussionmentioning
confidence: 99%